(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
The article explores the functions of accents, highlighting how they enrich linguistic diversity, support nonverbal communication, and contribute to empathy and cultural awareness. Accents also enhance media and storytelling by adding authenticity to characters and narratives, making stories more immersive. However, challenges like miscommunication and accent bias are acknowledged, underscoring the importance of embracing accent diversity to promote inclusivity. In sum, the article argues that accents are valuable components of human expression that bring vibrancy and understanding to communication, ultimately encouraging a more inclusive approach to language in a globalized world.